The evolution of glucose-insulin homeostasis in children with β-thalassemia major (β -TM): A twenty-year retrospective ICET- A observational analysis from early childhood to young adulthood - De Sanctis, Vincenzo; Daar , Shahina; Soliman , Ashraf T; Tzoulis , Ploutarchos; Karimi , Mehran; Kattamis , Christos (Acta Biomedica Atenei Parmensis, 2022)
Background: Thalassemia guidelines recommend oral glucose tolerance test (OGTT), starting from the age of 10 years, or earlier in the presence of iron overload. Objective: The aim of this retrospective study was to review and document the changes of glucose-insulin homeostasis from early childhood to young adulthood in β-thalassemia major (β -TM) patients with impaired fasting glucose (IFG) and normal OGTT. Methods: All data of the clinical patients’ records of 18 β -TM patients’ from September 1983 to September 2021 were included in the study. Annual or biennial OGTT results, for a duration of 15-20 years, were available for all patients. Results:The main findings are: a) IFG in children with β -TM represents a risk factor for the development of glucose dysregulation (GD) at later age; b) fluctuations of glucose homeostasis during follow-up were observed mainly in β-TM patients with IFG at baseline; and c) the primary defect of GD appears to be a low degree insulin resistance (IR), as estimated by HOMA-IR, followed by an insulin secretion defect. Conclusion:These results are noteworthy as they revealed that firstly, the baseline IFG predicts future development of GD, and secondly, that almost half of patients with IFG at the outset had normal glucose handling 15 years later. Understanding the sequence of abnormalities in the progression from normal glucose homeostasis to GD and identifying the risk factors for the glycometabolic defects in thalassemic patients might help in the formulation of interventions.